Noninvasive circulating tumor cell and urine cellular XPC (rs2228001, A2815C) and XRCC1 (rs25487, G1196A) polymorphism detection as an effective screening panel for genitourinary system cancers - Wu, Cen; Xu, Cheng; Wang, Guaxiu; Zhang, Dahu; Zhao, Xiaoyu (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: Valid cancer screening and treatment monitoring are critical for cancer patients. Although genitourinary system cancers have a high recurrence rate, when diagnosed, patients undergo surgery promptly. We sought to explore sensitive and noninvasive screening and postoperative recurrence monitoring methods, such as circulating tumor cells (CTCs) or tumor susceptibility gene detection, to determine their appropriateness for genitourinary system cancers. Methods: We adopted multiple detection methods. Enrichment-immunofluorescence in situ hybridization (SE-iFISH) was employed to detect CTCs from the peripheral blood of patients, and Agena Bioscience MassARRAY was used to detect single-nucleotide polymorphisms (SNPs) in tumor susceptibility genes from urine cells. Results: In our research, CTCs showed a 76.92% positivity rate among 26 genitourinary system cancer patients, and the number of CTCs was consistent with the stage of cancer. In monitoring for bladder cancer (BC) recurrence, CTCs were more prevalent than urine cytology (66.67% vs. 41.67%). To our surprise, urine cellular XPC (rs2228001, A2815C) and XRCC1 (rs25487, G1196A) polymorphisms were specifically found in cancer patients but not in patients with inflammation or in healthy individuals. XPC polymorphism (rs2228001, A2815C) rates were 30.77%, 40%, and 50% in bladder cancer, renal carcinoma, and prostate cancer patients, respectively, and those for XRCC1 (rs25487, G1196A) were 3.85%, 20%, and 25%, respectively. Conclusions: As a common biomarker, CTCs showed remarkable performance in cancer screening and monitoring. The noninvasive panel comprising CTCs and XPC (rs2228001, A2815C) and XRCC1 (rs25487, G1196A) polymorphisms showed high sensitivity (positive rate: 92.86%) and is suitable for genitourinary system cancer screening.